2009
DOI: 10.1016/j.topol.2008.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Completely normal frames and real-valued functions

Abstract: Up to now point-free insertion results have been obtained only for semicontinuous real functions. Notably, there is now available a setting for dealing with arbitrary, not necessarily (semi-)continuous, point-free real functions, due to Gutiérrez García, Kubiak and Picado, that gives point-free topology the freedom to deal with general real functions only available before to point-set topology. As a first example of the usefulness of that setting, we apply it to characterize completely normal frames in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In particular, for A = L we have A o(a) = o(a) and, therefore, both Theorem 3.7 of [11] and Proposition 3.3 of [14] follow: Corollary 5.3. The following are equivalent for any frame L:…”
Section: Heredity Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, for A = L we have A o(a) = o(a) and, therefore, both Theorem 3.7 of [11] and Proposition 3.3 of [14] follow: Corollary 5.3. The following are equivalent for any frame L:…”
Section: Heredity Propertiesmentioning
confidence: 97%
“…Complete normality formulated in frames appeared for the first time in the literature with [19] (see also [31]), in the following form: a frame is completely normal if every pair S, T of separated sublocales of L (i.e. such that S ∩ T = {1} = S ∩ T) is separated by open sublocales, that is, there exist open sublocales U and V of L such that U ∩ V = {1}, S ⊆ U and T ⊆ V. As proved in [11,Proposition 3.3], this is equivalent to condition (CN) above.…”
Section: Complete Extremal Disconnectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…After having introduced a localic analogue of the concept of an arbitrary (not necessarily continuous) real valued function (by Gutiérrez García et al [12]), we now have new areas of topology to be explored in the world of locales (cf. the very recent paper [8]). The motivation of this paper is the lack of localic variants of two topological results (the first of which involves arbitrary not necessarily continuous real valued function), viz.…”
Section: Introductionmentioning
confidence: 92%
“…Let L be a frame and F (L) := F rm(L(R), SL), where SL is the dual of the co-frame of all sublocales of L. In [10], they showed that the lattice ordered ring F (L) is a pointfree counterpart of the ring R X with X a topological space (also see [9,11]). They thus have a pointfree analogue of the concept of an arbitrary, not necessarily (semi) continuous, real function on L. In [25], they showed that F (L) = C(S c (L)) is always order complete, where S c (L) is a frame of closedly generated sublocales.…”
Section: Introductionmentioning
confidence: 99%